ROLE OF MRI IN EVALUATION OF EPILEPSY IN PEDIATRIC AGE GROUP IN A TERTIARY CARE CENTRE OF JHARKHAND, INDIA- A PROSPECTIVE STUDY. - Singh, Raghvendra Pratap; Ranjan, Rajeev Kumar; Rai, Nisha; Xalxo, Anima R.; Toppo, Suresh Kumar; Ram, Paras Nath (Student’s Journal of Health Research Africa, 2023)
Background: Childhood epilepsy is a prevalent neurological disorder. Imaging, especially MRI of the brain, plays a pivotal role in diagnosing the underlying cause. This study aimed to assess the frequency of causative factors of epilepsy detected in MRI. Materials and Methods: This hospital-based prospective observational study was conducted in the Radiology Department at Rajendra Institute of Medical Sciences (RIMS), Ranchi, Jharkhand, India from November 2021 to October 2022 in 100 children of 0 to 12 years of age referred from Pediatrics department for an MRI brain scan. MRI of the brain was performed in all cases and findings were analyzed and causes of epilepsy were assessed. Magnetic resonance spectroscopy (MRS) was also done when required for confirmation of diagnosis. Results: Positive findings in MRI were detected in 87% of children, and no abnormalities were detected in 13%. The majority of children belonged to the age group of 10-12 years (37%) and were predominantly males (66%). The most common cause of epilepsy was infections (27%) followed by hypoxic ischemic encephalopathy (22%). Tuberculoma was the most common infective cause of epilepsy in 59.3%. These were further followed by temporal lobe epilepsy and congenital malformations (11% each). The rest were other miscellaneous and idiopathic causes. Conclusion: MRI findings were specific to various conditions, helping in the localization and characterization of etiologies and playing a significant role in the evaluation of children who were newly diagnosed with epilepsy, especially those with partial seizures. Recommendation: Further research with a larger sample size and meta-analysis is recommended for more conclusive results.